Blind asynchronous multiuser CDMA receivers for ISI channels using code-aided CMA - Tugnait, J.K.; Tongtong Li (IEEE journal on selected areas in communications, 2001)
A code-aided constant modulus algorithm (CMA) based approach is presented for blind detection of asynchronous short-code DS-CDMA (direct sequence code division multiple access) signals in intersymbol interference (ISI)/multipath channels. Only the spreading code of the desired user is assumed to be known; its transmission delay may be unknown. A linear equalizer is designed by minimizing the Godard/CMA cost function of the equalizer output with respect to the equalizer coefficients subject to the fact that the equalizer lies in a subspace associated with the desired user's code sequence. Constrained CMA leads to the extraction of the desired user's signal whereas unconstrained minimization leads to the extraction of any one of the active users. The results are further improved by using unconstrained CMA initialized by the results of the code-aided CMA. Identifiability properties of the approach are analyzed. Illustrative simulation examples are provided.